(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Whatever wind and solar collection device designed to work mostly in low to mid-temperature area. Must include a solar collector at its core. As a result, an efficient solar collector system design with optimal performance is needed. Intelligent system design is a helpful method for optimizing the efficiency of such systems, even if many other strategies are used to improve system performance. Artificial Neural Network (ANN) is a kind of intelligence method that is utilized in system modeling, simulation, and control. In comparison to other traditional methods, the ANN tool solves difficult and nonlinear problems quicker and more accurately. The artificial neural network (ANN) method Economics, economics, art, military, trade, and technology are just a few of the sectors where it’s applied. Our ANN tool’s main task is model building, which will be done with the use of empirical observations. From solar energy systems, and this technique does not need separate programming like other traditional methods. The goal of this research is to look at how artificial intelligence (AI) may be used to forecast to assess the effectiveness of wind and solar collections and to review relevant requirements for the proposed study this same ANN approach is an excellent tool for forecasting solar panel function. Collector systems, as shown by the study reported in this article.